Torsion of pediatric indirect inguinal hernia sac: A rare case - Basem Saied Abdelkader; Mahmoud Ahmed Ahmed Abdelbary; Amer Nihal Ahmed (Elsevier, 2021)
Torsion of the hernia sac is a rare condition that presents as an acute scrotum. There are 11 cases reported in the English literature at the best of our knowledge, this case is the 12th case. We report a case, a 2.5 -year-old boy, who presented to the emergency room with tender right sided scrotal swelling. Ultra-sonography revealed intra-scrotal extra-testicular cystic lesion with normal right testis and epididimys. At surgery, a necrotic cyst with dark altered fluid was identified extending into the scrotum, it was connected to the peritoneal cavity, not connected to the testis or the epididymis, and it was twisted.